Hubungan Kemandirian dengan Kreativitas Siswa SMU - Soeparman Soeparman (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Relationship between Independence and Creativeness of Senior High School Students. The research was intended to test the correlation between the independence and the creativeness of SMU students. The sample consisted of 200 SMU students from Jember Municipality selected by proportional random sampling. The data were collected through a questionnaire and verbal test and then analyzed using regression analyses. The results indicate that there is a correlation between the independence of SMU students and their creativeness.